The chemical composition of dust transported in red rains—its contribution to the biogeochemical cycle of a holm oak forest in Catalonia (Spain) - Avila, a; Alarcon, M; Queralt, I (Atmospheric Environment, 1998)
The chemistry of North African dust reaching NE Spain with red rains is here described to (1) characterize the red dust elemental composition, (2) analyze the relative contribution of dissolved and particulate forms to the total element inputs for the period 1983–1994, and (3) study the role of the particulate and dissolved inputs in red rains to the forest nutrient cycle. Five dust samples, obtained from the filtration of five red rain events, have been considered as representative of the dust reaching NE Spain as they include dust from the main source regions in North Africa. Enrichment factors were lower than four for all elements and samples, indicating the crustal character of the red dusts and their scarce mixing with anthropogenic pollutants. Back trajectory analysis of the red rain air masses computed at various isentropic surfaces showed northward fluxes at all altitudes in four out of five events. The remaining event, which presented a lower layer from European origin contacting upper layers of North African provenance, had higher trace metal concentrations in the dust (still lower than reported values for the circum-Mediterranean area) and higher S and N concentrations in dissolved form. The occurrence of red rains introduced high interannual variability in the input fluxes for the major elements. Phosphorus inputs occurred mostly in particulate form linked to red dust deposition. Red dust particulate inputs were also important for K+ and Mg2+. For Ca2+, dissolved inputs in red rains equalled and sometimes overuled particulate inputs in red dust, due to the calcite dissolution. Sodium and S inputs in red rains were mostly in dissolved form. The amounts of base cations delivered by red rains are important contributors to the holm oak forest needs at Montseny, by providing 27% of K+, 45% of Ca2+ and 84% of Mg2+ fluxes needed for the above ground biomass annual increment. For Ca2+ this is specially relevant because of the calcium-poor lithology of the site
Keywords: aerosol composition; Back trajectories; forest biogeochemistry; nutrient inputs; Saharan dust

Mineralogical composition of African dust delivered by red rains over northeastern Spain - Avila, a; QueraltMitjans, I; Alarcon, M (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 1997)
The African dust deposition, mineralogy, source regions, and influence on rain chemistry were analyzed for a site in the Montseny mountains (Catalonia, northeastern Spain) for the period August 1, 1983, through August 1, 1994. Dust deposition was highly variable: two events (collected on November 9-11, 1984, and March 22-25, 1991) accounted for 62% of the total dust input in the 38 red rain events recorded in the period. The average annual dust deposition was 5.3 g m(-2) (SE 2.6). Three source regions in the African continent were identified with back trajectory analysis: (1) Western Sahara, (2) Moroccan Atlas, and (3) Central Algeria. Events from the Moroccan Atlas predominated in terms of number of events, amount of rainfall, and dust deposition. The meteorological situations during red rains were identified: Western Sahara events occurred principally with a depression at high latitudes (50 degrees N) forming a trough in the North Atlantic, Moroccan Atlas events occurred with a depression in front of Portugal, and events from central Algeria were associated with a depression over Spain or North Africa. By order of abundance (median of n=13) the minerals identified in the dust by X ray diffraction were as follows: illite > quartz > smectite > palygorskite > kaolinite > calcite > dolomite > feldspars. Differences in mineralogy between source regions were significant for smectite, kaolinite, quartz, and dolomite. Smectite and kaolinite content was highest in the Algerian events, while quartz and dolomite content was lowest. Events from the Moroccan Atlas had the lowest smectite and kaolinite. The red rain soluble chemistry was clearly influenced by the dissolution of calcite (high alkalinity, calcium concentration and basic pH) and by marine components (high Na+, Cl- and Mg+2 concentrations). Because of the very alkaline character of red rains they had a strong weight on the annual mean pH of rainwater. This was reflected by the significant relationship (r=0.71, p<0.01) between the percentage of annual precipitation as red rain and annual mean precipitation pH. Red rains provided 25-45% of the annual dissolved input of the major ions in precipitation and 34% of the calcium required for helm oak (Quercus ilex L.) forest growth at the study site.
APS
Keywords: Africa; dust deposition; Montseny mountains; Quercus ilex L.